2012
DOI: 10.21608/ejp.2012.103180
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Thaxtomin A Production by Streptomyces scabies in Egypt

Abstract: wenty isolates of Streptomyces scabies were isolated from scab lesions on potato tubers collected from three different regions in Behera Governorate during the 2009-2010 growing season. The isolates of S. scabies recovered were totally monomorphic for the morphological and the biochemical characteristics investigated. All isolates were non motile, gram positive, exhibited grey colonies, spiral spore chain and were melanin producers. Meantime the isolates showed positive reaction for catalase activity, starch h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 17 publications
(30 reference statements)
1
5
0
Order By: Relevance
“…These results were in harmony with earlier studies that found variations in virulence among Streptomyces spp., notably S. scabies isolates (Wanner, 2004;Dees et al, 2013;Karagöz and Kotan, 2017;Shi et al, 2019). In former research conducted in Elbeheira Governorate of Egypt, El-Sheikh et al (2012) identified 20 isolates of S. scabies with five that were highly virulent and 15 were moderately virulent based on scab index on potato mini tubers. Also, Hussein et al (2019) isolated 12 isolates of S. scabies that differed in their virulence on potato plants.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These results were in harmony with earlier studies that found variations in virulence among Streptomyces spp., notably S. scabies isolates (Wanner, 2004;Dees et al, 2013;Karagöz and Kotan, 2017;Shi et al, 2019). In former research conducted in Elbeheira Governorate of Egypt, El-Sheikh et al (2012) identified 20 isolates of S. scabies with five that were highly virulent and 15 were moderately virulent based on scab index on potato mini tubers. Also, Hussein et al (2019) isolated 12 isolates of S. scabies that differed in their virulence on potato plants.…”
Section: Discussionmentioning
confidence: 99%
“…Inocula suspensions were prepared at approximately 1 x 10 7 spore/ ml tryptone yeast broth medium, and 50 ml of inoculum of each isolate were mixed with 1.5 L of autoclaved vermiculite (Balcony garden, Egypt). This mixture was added to 20 potato mini tubers in small plastic bags, incubated for 14 days, and shaken many times during the incubation period (El-Sheikh et al, 2012). Clean potato mini tubers were served as control.…”
Section: Virulence Assays Of Selected S Scabies Isolates: Common Scab...mentioning
confidence: 99%
See 3 more Smart Citations